The Impact Of Work Shifts, Organizational Culture, And Workload On The Performance Of Contract Nurses At Bhayangkara Tebing Tinggi Hospital - Gultom, Richad; Wahyu Ginanjar; Aisyah Siregar; Rapat Piter Sony Hutauruk (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this study was to determine the effect of work shifts , organizational culture and workload on the performance of nurses at Bhayangkara Tebing Tinggi Hospital. The sample in this study was nurses at Bhayangkara Tebing Tinggi Hospital. The sampling technique used was the Non Probability Sampling technique using the Slovin formula totaling 54 people. The data collection technique in this study used a questionnaire and literature study. The data analysis technique in this study used the classical assumption test, multiple linear regression test, hypothesis test and statistical test using the SPSS version 25 application. Based on the results of the study and discussion in this study, it is known that the variables of work shifts , organizational culture and workload have an effect on the nurse performance variable.